2024
DOI: 10.3390/tropicalmed9020032
|View full text |Cite
|
Sign up to set email alerts
|

The Spatiotemporal Distribution and Molecular Characterization of Circulating Dengue Virus Serotypes/Genotypes in Senegal from 2019 to 2023

Idrissa Dieng,
Cheikh Talla,
Mamadou Aliou Barry
et al.

Abstract: Dengue virus is becoming a major public health threat worldwide, principally in Africa. From 2016 to 2020, 23 outbreaks were reported in Africa, principally in West Africa. In Senegal, dengue outbreaks have been reported yearly since 2017. Data about the circulating serotypes and their spatial and temporal distribution were limited to outbreaks that occurred between 2017 and 2018. Herein, we describe up-to-date molecular surveillance of circulating DENV serotypes in Senegal between 2019 to 2023 and their tempo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The sequences from Senegal were generated using both Nanopore et Illumina sequencing technologies. Details can be found here (Idrissa Dieng et al 2022Dieng et al , 2024. Methods for generating sequences from Brazil can be found here (Bermann et al 2024) and from Tanzania can be found here (Kelly et al 2023).…”
Section: Case Studiesmentioning
confidence: 99%
“…The sequences from Senegal were generated using both Nanopore et Illumina sequencing technologies. Details can be found here (Idrissa Dieng et al 2022Dieng et al , 2024. Methods for generating sequences from Brazil can be found here (Bermann et al 2024) and from Tanzania can be found here (Kelly et al 2023).…”
Section: Case Studiesmentioning
confidence: 99%